FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN WUS TENTANG SKRINING PAP SMEAR DI KELURAHAN POMPANUA KECAMATAN AJANGALE KABUPATEN BONE - Mustar (LPPM Institut Sains dan Kesehatan Bone, 2015)
ABSTRACT; Factors associated with WUS knowledge about screening of Pap Smear At the District Pompanua village Ajangale Bone. Pap smear at this time is a necessity for a woman, as a means of prevention and early detection of cervical cancer. is a Pap smear is the study of cells separated or desquamation of the female womb tool systems, including cells that are separated from the vagina, cervix, endocervical, and endometrium.Jenis research used survey method with the analytical approach, which intended as guidelines for the survey to find out is there a relationship between age, education, and social culture of the WUS knowledge about screening of Pap smears. The population is all women of childbearing age who are in the Village Pompanua in 2013 that is 450 people and the sample is part of the Women of fertile age who are in the Village Pompanua in 2013 that is 212 people. Based on the results of this study concluded that there is a relationship between age signifikanan with a P value of 0.00, which means there is a relationship between age and knowledge, and views of the educational factors with a P value of 0.00, which means there is a relationship between education and knowledge as well as the last of socio-cultural factors with a P value of 0.00, which means there is a relationship between socio-cultural with knowledge of the WUS knowledge of Pap smear screening. This indicates that the level of knowledge of a WUS is influenced by three factors namely age, education and culture Social WUS